Penerapan Website E-Government Dalam Pendataan Infrastruktur Dan Fasilitas Publik - Rakhmansyah, Mohamad; Sari, Meri Mayang; Andwiyan, Denny (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
The development of science and technology in the management system of social and public facilities will assist in improving the performance of the sub-district government. Currently, the Pasar Kemis District office does not yet have a web-based infrastructure and facility management system to overcome the problem of collecting data on social and public facilities that still use a semi-computer system, namely recording infrastructure and facility data using paper, then recapitulation is carried out to make reports on social facilities. And general. This system still has shortcomings such as difficulty in finding data, allowing errors in data collection, data piling up and requiring a long time in the reporting process. To overcome the problems faced, the authors propose a web-based social and public facility management system so that data collection on facilities becomes easier, shortens time, is organized in data storage. The author uses the method of Observation, Interview, and Literature Study in collecting data. All data are summarized and then clearly described in the Unified Modeling Language (UML). Making a prototype system using Adobe XD application and in analyzing the advantages and disadvantages of the system, the researcher uses the SWOT method. This system is made using the PHP programming language with the Codeigniter framework. The system was tested using the Black Box Testing method. The computerized system makes it easier to manage infrastructure and facilities data so as to assist in the data collection process, data retrieval and reporting of social and public facilities.